Bioactive profiling of Rumex vesicarius L. from the Hail region of Saudi Arabia: a study on its phytochemical and elemental analysis, antibiofilm, antibacterial, antioxidant properties, and molecular docking analysis - Sulieman, Abdel Moneim Elhadi; Abdallah, Emad M.; Alanazi, Naimah Asid; Idriss, Hajo; Adnan, Mohd; Jamal, Arshad; Shommo, Sohair A. M.; Snoussi, Mejdi (Frontiers in Microbiology, 2024)
Rumex vesicarius is a wild leafy plant classified under the family Polygonaceae, recognized for its therapeutic benefits. The genus Rumex, belonging to the family Polygonaceae, consists of approximately 150 species extensively scattered across the globe. In the present study, we aimed to investigate the biological activities of this plant using in vitro and in-silico methods. R. vesicarius was collected from the mountains in Hail and extracted with methanol. "Utilizing conventional methods," the colorimetric detection method was employed to qualitatively determine the phytochemical composition, elemental analysis, in silico docking analysis, antioxidant, antibacterial, and antibiofilm properties. The extract contained various classes of phytochemicals, including flavonoids, phenolics, tannins, terpenes, and saponins. Sixteen constituents were identified with molecular docking, revealing inhibition against the filamentous temperature-sensitive protein Z (FtsZ), a crucial factor in bacterial cell division. Six compounds exhibited low binding scores ranging from -8.3 to -5.0 kcal/mol, demonstrating efficiency in interaction at the active site. The elemental analysis identified 15 elements, with potassium being the most abundant, followed by calcium, aluminum, silicon, ferrous, phosphorous, sulfur, magnesium, titanium, strontium, zinc, manganese, bromine, and Chromium. Antioxidant analysis revealed significant antioxidant properties at lower concentrations than ascorbic acid, butylated hydroxytoluene, and β-carotene. Antibacterial analysis (in vitro) demonstrated inhibitory effects on Bacillus subtilis (B. subtilis) MTCC121 and Pseudomonas aeruginosa (P. aeruginosa) MTCC 741, with inhibition zones measuring 13.67±1.0 mm and 11.50±1.0 mm, respectively. M.I.C. and M.B.C. values ranged from 250 to 500 µg/mL. R. vesicarius also exhibited antibiofilm activity. In conclusion, wild-grown R. vesicarius in the mountains of Hail is rich in bioactive phytochemicals and essential minerals, exhibiting antioxidant and antibacterial characteristics.